2023
DOI: 10.2147/dddt.s379964
|View full text |Cite
|
Sign up to set email alerts
|

Bulevirtide in the Treatment of Hepatitis Delta: Drug Discovery, Clinical Development and Place in Therapy

Abstract: It has been ten years since the identification of NTCP as the cell surface receptor for HBV and HDV entry into hepatocytes. The search for molecules interfering with the binding of NTCP and HBV/HDV led to design bulevirtide (BLV). This large polypeptide mimics a region of the pre-S1 HBsAg and blocks viral entry by inhibitory competition. BLV was initially tested in cell cultures, animal models and more recently in Phase I–III human trials (called ‘MYRS’). As monotherapy or in combination with peginterferon, BL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…Benefits to earlier HDV screening and detection include earlier initiation of HDV therapy and closer monitoring for liver‐related complications, which may improve clinical outcomes. With the advent of novel HDV therapies on the horizon, our findings emphasize the importance of HDV serological screening and reflex RNA testing among PWH with HBV coinfection, especially those with a history of IDU 26–28 …”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Benefits to earlier HDV screening and detection include earlier initiation of HDV therapy and closer monitoring for liver‐related complications, which may improve clinical outcomes. With the advent of novel HDV therapies on the horizon, our findings emphasize the importance of HDV serological screening and reflex RNA testing among PWH with HBV coinfection, especially those with a history of IDU 26–28 …”
Section: Discussionmentioning
confidence: 79%
“…With the advent of novel HDV therapies on the horizon, our findings emphasize the importance of HDV serological screening and reflex RNA testing among PWH with HBV coinfection, especially those with a history of IDU. [26][27][28] Our study has several potential limitations. First, selection bias is possible since only patients who had an available serum/plasma sample on or after their initial HBV test were included.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…As hepatitis delta is the most aggressive of all chronic viral hepatitis, most PLWH with hepatitis delta progress to liver cirrhosis and may develop liver cancer 61,62 . No effective antiviral therapy had been developed until recently to treat hepatitis delta, but the advent of a subcutaneous entry inhibitor, bulevirtide, has opened a new era for hepatitis delta 83 (Table 2).…”
Section: Interventions To Reduce the Burden Of Viral Hepatitis In Plwhmentioning
confidence: 99%
“…It blocks the NTCP receptor at the hepatocyte surface, causing inhibitory competition with the physiologic substrate, the bile acids. In several clinical trials, bulevirtide has demonstrated excellent tolerability and minimal side effects [ 24 ]. Serum HBV-DNA goes down in most treated patients; however, no effect is seen on serum HBsAg concentrations.…”
Section: New Hbv Antiviralsmentioning
confidence: 99%